Metabolite Profiling of adh1 Mutant Response to Cold Stress in Arabidopsis - Song, Yuan; Liu, Lijun; Wei, Yunzhu; Li, Gaopeng; Yue, Xiule; An, Lizhe (Frontiers in Plant Science, 2017)
As a result of global warming, vegetation suffers from repeated freeze-thaw cycles caused by more frequent short-term low temperatures induced by hail, snow, or night frost. Therefore, short-term freezing stress of plants should be investigated particularly in light of the current climatic conditions. Alcohol dehydrogenase (ADH) plays a central role in the metabolism of alcohols and aldehydes and it is a key enzyme in anaerobic fermentation. ADH1 responds to plant growth and environmental stress; however, the function of ADH1 in the response to short-term freezing stress remains unknown. Using real-time quantitative fluorescence PCR, the expression level of ADH1 was analyzed at low temperature (4 °C). The lethal temperature was calculated based on the electrolyte leakage tests for both ADH1 deletion mutants (adh1) and wild type (WT) plants. To further investigate the relationship between ADH1 and cold tolerance in plants, low-Mr polar metabolite analyses of Arabidopsis adh1 and WT were performed at cold temperatures using gas chromatography-mass spectrometry. This investigation focused on freezing treatments (cold acclimation group: -6 °C for 2 h with prior 4 °C for 7 d, cold shock group: -6 °C for 2 h without cold acclimation) and recovery (23 °C for 24 h) with respect to seedling growth at optimum temperature. The experimental results revealed a significant increase in ADH1 expression during low temperature treatment (4 °C) and at a higher lethal temperature in adh1 compared to that in the WT. Retention time indices and specific mass fragments were used to monitor 263 variables and annotate 78 identified metabolites. From these analyses, differences in the degree of metabolite accumulation between adh1 and WT were detected, including soluble sugars (e.g. sucrose) and amino acids (e.g. asparagine). In addition, the correlation-based network analysis highlighted some metabolites, e.g., melibiose, fumaric acid, succinic acid, glycolic acid, and xylose, which enhanced connectedness in adh1 network under cold chock. When considered collectively, the results showed that adh1 possessed a metabolic response to freezing stress and ADH1 played an important role in the cold stress response of a plant. These results expands our understanding of the short-term freeze response of ADH1 in plants.